A Classical Approach to Artificial Intelligence (New Delhi: Khanna Publishing House, 2008)
There are many books available in The market on The proposed topic but none of them can be termed as comprehensive. Besides, students face many problems in understand The language of This books. Keeping these points in mind, artificial intelligence was prepared, which should be simple enough to comprehend and Comprehensive enough to encompass all The topics of different institutions and universities. table of content1 - overview of artificial intelligence - problem solving and search3 - search Methods 4 - problem solving in games (adversarial search) 5 - understand natural languages - knowledge representation 7 - techniques of knowledge Representation8 - expert System 9 - pattern recognition - computer vision11 - computer vision representations12 - common sense 13 - programming languages.
"Prof. Munesh C. Trivedi has completed his graduation & post graduation in Computer Science and Ph. D. degree in Computer Science. He started his teaching career in engineering education from IEC College of Engineering & Technology, Greater Noida. India. He also served Krishna Institute of Engineering & Technology, Ghaziabad and I.I.T Kanpur as a Project Associate. Presently he is working in Institute of Management Studies, Ghaziabad, India since sept. 2007. He has rich experience in teaching the undergraduate and postgraduate classes. He has published 16 text books and he has been declared Author of Year 2008 as per Books Today survey. He has published more than 25 journal and conference papers in the area of Fractals, image processing, e-learning. He has delivered numerous invited and plenary conference presentations and seminars through Country and chaired the technical sessions in International and national conferences in India. He has delivered many invited talks in India. He is on the review panel of International Journal of Network Security and Computer & Education (Elsevier's Journal). He has been the member of board of studies of different Indian universities and member of organizing committee for various national and international seminars/workshops. He is member of CSI, IAE, and life member of ISTE."
Keywords: Computers - Computer Science